Sistem Kontrol Pintu Otomatis Menggunakan RFID (Radio-Frequency Identification) Berbasis Internet of Things (IoT) - Rahman, M Fadhilur; Rahman, Moh Irfan Auliya (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
The rapid growth in the number of motor vehicles within the Universitas Nurul Jadid environment has created several challenges in parking management, including vehicle queues at entry and exit gates, manual parking data recording, and limited system capabilities in ensuring vehicle security and continuous monitoring. Conventional parking systems that rely heavily on human operators are considered ineffective and inefficient, particularly in supporting integrated and data-driven parking management. This study aims to design and develop an automatic parking gate system based on Radio Frequency Identification (RFID) and Internet of Things (IoT) technologies at Universitas Nurul Jadid. The proposed system utilizes RFID cards as user identification media, an ESP32 microcontroller as the main controller, vehicle detection sensors, and a servo motor as the actuator for opening and closing the gate. User identity data and parking activity records are transmitted in real time via an internet connection to an IoT server and presented through a web-based monitoring dashboard. The research method employed is an engineering approach, which includes requirements analysis, system design, hardware and software implementation, and functional system testing. The test results indicate that the system is capable of performing fast and accurate user identification, automatically operating the parking gate, and recording and displaying parking data in real time. The implementation of this system has been proven to improve parking service efficiency, reduce vehicle queues, and support safer and more structured parking management. The developed system is expected to serve as a supporting solution for the implementation of the smart campus concept at Universitas Nurul Jadid.